Worst‐Case Severe Environments for Surface Charging Observed at LANL Satellites as Dependent on Solar Wind and Geomagnetic Conditions. Issue 9 (22nd September 2021) - Ganushkina, N. Yu; Swiger, B.; Dubyagin, S.; Matéo‐Vélez, J.‐C.; Liemohn, M. W.; Sicard, A.; Payan, D.
Abstract: The 400 worst‐case severe environments for surface charging detected at Los Alamos National Laboratory satellites during the years of 1990–2005 as binned by the definitions of four criteria developed by Matéo‐Vélez et al. (2018, https://doi.org/10.1002/2017sw001689 ) and the solar wind and Interplanetary Magnetic Field (IMF) parameters and geomagnetic activity indices are analyzed. The conducted analysis shows that only Auroral Electrojet/Auroral Lower index determines the highest risk for severe environments for surface charging to happen. The presence of a substorm with the southward turning pattern in IMF B z indicates that the environment can be severe for surface charging to occur but this environment will not depend on whether a substorm was moderate or intense. No clear dependence on IMF B z is found for risk to a severe environment to occur. Appearances of severe environments for surface charging do not necessarily require high values of Kp (Planetarische Kennziffer) and no storm is needed for such an event to be detected. Among solar wind parameters, solar wind velocity V s w is directly related to the highest risk of severe environments, dependent on the V s w value; and number density N s w is of no importance. Two criteria for severe environment events based on the enhancements of low energy particle fluxes exhibit clearer dependencies on the solar wind and IMF parameters and geomagnetic activity indices with more distinct patterns in their time history. Plain Language Summary: In spite of recent engineering and technological advancements, modern satellites are still subject to dangerous influence from radiation due to the presence of high energy particles in the near‐Earth space. These particles can cause accumulation of some charge on the satellite's surfaces. They vary a lot depending on the activity on the Sun. The solar activity can be characterized by several parameters. Relating the detected surface charging events to the parameters can help to predict the occurrence of these events based on knowing the solar activity. The 400 worst‐case severe environments for surface charging detected at Los Alamos National Laboratory satellites during the years of 1990–2005 were analyzed and related to solar activity. It was found that surface charging can occur during rather moderately disturbed conditions, and presence of a strong disturbance does not necessarily lead to satellite anomalies. Solar wind velocity and its magnitude can be a direct indicator for the highest risk of severe environments for surface charging. Key Points: Presence, not magnitude, of substorm activity (as Auroral Electrojet/Auroral Lower index) is the strongest characteristics for severe environments for surface charging Occurrence of even a moderate storm is not necessary for severe environments for surface charging to occur Solar wind velocity and its magnitude are the direct indicator for the highest risk of severe environments for surface charging